The Federal Trade Commission Against Facebook : a law and society approach to consumer privacy and competition policy - Fonseca, Mariana Moutinho (2021)
Dissertação (mestrado)—Universidade de Brasília, Faculdade de Direito, Programa de Pós-Graduação em Direito, 2021.